Oxford handbook of clinical medicine - Longmore, Murray (Oxford University Press, 2010)
Oxford Handbook of Clinical Medicine is a guiding star for all medical students, junior doctors and trainees. The culmination of more than 20 years' clinical experience, and containing the knowledge and insight gained by more than 15 authors, the new eighth edition continues to be the definitive pocket-sized guide to today's clinical medicine. Packed with clear, clinical management advice which is practical to implement at the bed-side, the Oxford Handbook of Clinical Medicine is written in a clear and didactic style. With witty, esoteric asides linking medicine to everything from the classics to popular culture, all the material is presented in a way that is instantly memorable and even easier to put into practice. With extensive improvements based on reader feedback, the new eighth edition boasts even more black and white and full-colour images, which are now larger to improve their clarity and ease-of-use. Mindful of how doctors' training is constantly evolving, a new chapter on 'history and examination' explores this relevant critical skill in depth, enabling you to elicit as much information from the patient as possible. An expanded radiology chapters features improved images, and new topics are devoted to new cancers such as nosocomial infections, and further common surgical procedures. The references have been thoroughly overhauled with 'key references' identifying the best places to start when researching the subject, and all references are fully accessible via the supporting website. Loved and trusted by generations of doctors, the Oxford Handbook of Clinical Medicine is a reassuring beacon of wisdom, knowledge and skills, that is forever in your sights.